Disinfection of synthetic and real municipal wastewater effluent by flow-through pulsed UV-light treatment systems - Uslu, Gulsad; Demirci, Ali; Regan, John M. (American Society of Agricultural and Biological Engineers, 2014)
Pulsed UV-light technology has been proposed as an alternative to chlorine and conventional UV light treatments to inactivate microorganisms in wastewater effluent. Therefore, this study was undertaken to characterize the efficacy of flow-through pulsed UV light for inactivation of Escherichia coli and Bacillus subtilis spores in synthetic (SMWE) and real municipal wastewater effluent (RMWE). The results show that complete inactivation was observed with a 10 L/min flow rate for E. coli and 6 L/min flow rate for B. subtilis using one-pass pulsed UV treatment and SMWE. For two-pass treatment and SMWE, complete inactivation was observed with a 16 Umin flow rate for E. coli and 10 L/min flow rate for B. subtilis. Sterile RMWE inoculated with E. coli and B. subtilis spores was also treated by the flow-through pulsed UV light treatment at 10 Umin flow rate for E. coli and 6 Umin for B. subtilis. Complete inactivation was observed (7.58 Log reduction) for 10 L/min flow rate treatments of E. coli, whereas 4.15 Log reduction was observed for B. subtilis for one pass. The raw wastewater was also treated under flow-through pulsed UV light at 10 L/min flow rate and complete inactivation was observed (7.4 Log reduction). The SMWE with 10% E. coli or B. subtilis was analyzed for COD, TOC, and turbidity before and after flow-through pulsed UV treatment at the determined optimum conditions. The treatment resulted in COD reductions of 28.7 and 20.2% for E. coli and B. subtilis, respectively. Also, results indicated that COD decreased by 45.7 and 39.4%, respectively, for cell-free SMWE (uninoculated) after 10 L/min for E. coli and 6 L/min for B. subtilis, respectively. TOC removal was determined as 42.5 and 27.1% for E. coli and B. subtilis, respectively. Also, results indicated that TOC decreased by 48.9 and 35.5%, respectively, for cell-free SMWE (uninoculated) after 10 L/min under pulsed UV treatment for E. coli and 6 Umin for B. subtilis, respectively. These results clearly indicate that pulsed UV not only disinfects successfully the wastewater effluent, but also reduces organic load of municipal wastewater effluent. Therefore, pulsed UV technology can be an alternative for chlorine and conventional UV light for municipal wastewater effluent. Copyright © (2014) by the American Society of Agricultural & Biological Engineers All rights reserved.
American Society of Agricultural and Biological Engineers Annual International Meeting 2014, ASABE 2014 -- 13 July 2014 through 16 July 2014 -- Montreal -- 108722
Keywords: B. subtilis; Disinfection; E. coli; Flow-through Pulsed UV; Inactivation; Synthetic and real wastewater